Identification and Characterization of Differentially Expressed Genes in Ganoderma Boninense-Infected Oil Palms (Elaeis Guineensis) - Balia Yusof, Zetty Norhana (2007)
Basal stem rot (BSR) caused by Ganoderma boninense is the most serious disease of oil palms in Malaysia. Thus, changes in the gene expression patterns of infected palms have gained interests among researchers as a tool to understand the disease. An indication that there are differences in susceptibility to BSR between germplasm materials from different genetic origins have provided hope in generating oil palm varieties with reduced levels of susceptibility by using existing genetic materials. The study of differentially expressed genes may also pave the way towards developing diagnostic tools for early disease detection in oil palms. A novel method combining elements of suppression subtractive hybridization (SSH) permits the efficient and rapid cloning of rarely transcribed differentially expressed genes. The experimental strategy virtually excludes the possibility of isolating false positive clones. This study used SSH and isolated 1,038 differentially expressed cDNAs from the G. boninense-inoculated oil palm seedlings (T1) when subtracted from its uninoculated counterpart (T2), using the basal stem and spear leaf tissues. Sequence data indicated that of the 1,038 clones obtained, 86% showed sequence similarity to proteins already registered in public databases, 10% showed similarity to putative protein sequences and 4% were unknown proteins with no records in public databases. Seven clones harboring genes encoding for defense mechanisms against fungal and insect pathogens in plants were identified. They were pathogenesis-related (PR)-genes and defense-related genes depending on their direct or indirect roles in plant defense against pathogens. Reverse northern analysis of these 7 clones demonstrated that 4 were differentially expressed in T1 but northern analysis showed that only 3 were differentially expressed. Further analysis via reverse transcription-PCR (RT-PCR) confirmed these 3 genes to be differentially expressed in G. boninense infected oil palms. They were MAG 43 that codes for serine palmitoyltransferase, MAG 59 for chitinase and MAG 225 for endochitinase.